2018
DOI: 10.3389/fimmu.2017.01792
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Apoptosis Protein Antagonists (Smac Mimetic Compounds) Control Polarization of Macrophages during Microbial Challenge and Sterile Inflammatory Responses

Abstract: Apoptosis is a physiological cell death process essential for development, tissue homeostasis, and for immune defense of multicellular animals. Inhibitors of apoptosis proteins (IAPs) regulate apoptosis in response to various cellular assaults. Using both genetic and pharmacological approaches we demonstrate here that the IAPs not only support opportunistic survival of intracellular human pathogens like Chlamydia pneumoniae but also control plasticity of iNOS+ M1 macrophage during the course of infection and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Apart from these, we have validated several other immune adjuvants, such as low dose Gamma Radiation (Klug et al, 2013;Prakash et al, 2016), S-1P (Nadella et al, 2019), and Smac mimetics (Nadella et al, 2017), which indicate the potential of the Th1 programming of macrophages in a pre-clinical model system. These adjuvants are likely to create immunity against SARS-CoV-2 infection in the animal models discussed above.…”
Section: Proposed Interventionmentioning
confidence: 98%
“…Apart from these, we have validated several other immune adjuvants, such as low dose Gamma Radiation (Klug et al, 2013;Prakash et al, 2016), S-1P (Nadella et al, 2019), and Smac mimetics (Nadella et al, 2017), which indicate the potential of the Th1 programming of macrophages in a pre-clinical model system. These adjuvants are likely to create immunity against SARS-CoV-2 infection in the animal models discussed above.…”
Section: Proposed Interventionmentioning
confidence: 98%
“…We [52] and others [53,54,55] have previously demonstrated that many pathogenic microbes which are associated with cancer reprogram macrophages immunologically and metabolically during persistency. Apart from this, many pathogenic bacteria/viruses like Helicobacter pylori , Fusobacterium nucleatum , and Chlamydia sp.…”
Section: Change In the Gut Microbiome Triggers Tlr Mimicry And Promentioning
confidence: 99%
“…In in vitro models, metformin, a widely used antidiabetic agent, has been shown to inhibit TNF production by monocytes ( Arai et al, 2010 ), affect macrophage polarization ( Nadella et al, 2017 ), and promote autophagy ( Singhal et al, 2014 ). It affects Th1 responses, but data are conflicting: in mice infected with TB, metformin treatment promotes the expansion of Mtb -specific IFN-γ secreting T cells in the lungs ( Singhal et al, 2014 ), whereas in human THP-1 cells (not infected with Mtb ) metformin suppressed the production of Th1-related cytokines ( Chen et al, 2018 ).…”
Section: Medicines Used In Other Human Diseases As Host-directed Thermentioning
confidence: 99%